ASSOCIATION BETWEEN PSYCHOLOGICAL STRESS AND SKIN SYMPTOMS AMONG MEDICAL STUDENTS STUDYING IN KARACHI - Imam, Mustafa Hussain; Karatela, Muzzamil Ahmed; Kamal, Muskan; Baig, Muskan; Shah, Muhammed Aalam; Barry, Muhammad Umer; Hussain, Muhammad Shoaib; ali, Muhammad Yahya ayan; Umm-e-Rabab (Journal of Pakistan Psychiatric Society, 2023)
OBJECTIVE: To determine any association between psychological stress and skin symptoms in medical students.DESIGN OF STUDY: It is a cross-sectional studyPLACE AND DURATION: The study was conducted over a period of 12 months, from 30th September 2022 to 1st August 1 2023, on medical students enrolled in the MBBS programme at Liaquat National Hospital and Medical College.METHOD: We studied medical students through self-reported, validated questionnaires that inquired about socio-demographic information, perceived stress, and skin complaints. Data analysis was done on SPSS version 22, and descriptive frequencies presented as the mean and standard deviation. Associations were assessed by applying the chi-square test among the variables.RESULTS: A total of 401 questionnaires were used to analyse the data, with a mean age of 20.9 (SD =1.6). We found that 15.7% (n = 28) of the medical students were highly stressed, 77.3% (n = 310) were moderately stressed, and 7% (n = 63) were under low stress. The most common skin symptoms among medical students were hair fall (76.6%) (n = 315) and dark circles (77.3%) (n = 314). Individuals with high PS levels were more likely to develop skin symptoms such as itchy skin on the hands (p = 0.005), pimples or acne (p = 0.049), troublesome sweating (p = 0.04), dark circles (p = 0.01), and hair greying (p = 0.035).CONCLUSIONS: Psychological stress is associated with skin symptoms reported by medical students, especially dark circles, loss of hair, greying of hair, troublesome sweating, and itchy rashes on the hands. Further studies and interventions should be done to assess and assist medical students.